A meta-analysis of efﬁcacy and safety of doripenem for treating bacterial infections - Qu,Xiao-Yu (2015)
Objective: The aim of this article is to compare the efﬁcacy and safety of doripenem for bacterial infections. Methods: We included six randomized clinical trials identiﬁed from PubMed and Embase up to July 31, 2014. The included trials compared efﬁcacy and safety of doripenem for complicated intra-abdominal infections, complicated urinary tract infection, nosocomial pneumonia, and acute biliary tract infection. The meta-analysis was carried on by the statistical software of Review Manager, version 5.2. Results: Compared with empirical antimicrobial agents on overall treatment efﬁcacy, doripenem was associated with similar clinical and microbiological treatment success rates (for the clinical evaluable population, odds ratio [OR] = 1.26, 95% conﬁdence interval [CI] 0.93-1.69, p = 0.13; for clinical modiﬁed intent-to-treatment population, OR = 0.88, 95% CI 0.55-1.41, p = 0.60; for microbiology evaluable population, OR = 1.16, 95% CI 0.90-1.50, p = 0.26; for microbiological modiﬁed intent-to-treatment (m-mITT), OR = 0.98, 95% CI 0.81-1.20, p = 0.87). We compared incidence of adverse events and all-cause mortality to analyze treatment safety. The outcomes suggested that doripenem was similar to comparators in terms of incidence of adverse events and all-cause mortality on modiﬁed intent-to-treatment population (for incidence of AEs, OR = 1.10, 95% CI 0.90-1.35, p = 0.33; for all-cause mortality, OR = 1.08, 95% CI 0.77-1.51, p = 0.67). In nosocomial pneumonia and ventilator-associated pneumonia treatment, doripenem was not inferior to other antibacterial agents in terms of efﬁcacy and safety. Conclusion: From this meta-analysis, we can conclude that doripenem is as valuable and well-tolerated than empirical antimicrobial agents for complicated intra-abdominal infections, complicated urinary tract infection, acute biliary tract infection and nosocomial pneumonia treatment.